Novel Preparation of Hemiaminal Derivatives with BPO and N, N‐Dimethylamides and Their Synthetic Use for (Aminomethyl)indoles. Issue 30 (30th July 2020) - Nakamura, Kohei; Togo, Hideo
Abstract : A novel preparation of hemiaminal derivatives bearing both an amide group and a benzoate group was carried out in good yields by the treatment of BPO in N, N ‐dimethylamides under warming condition at 80 °C or irradiation with a mercury lamp. Further treatment of the obtained hemiaminal derivatives with indoles in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol generated the corresponding C–C bonded indoles bearing an amide group in good yields. The formed indoles bearing an amide group were smoothly transformed into the corresponding indoles bearing an aminomethyl group. Abstract : Hemiaminal derivatives could be obtained in good yields by the reaction of BPO and N, N ‐dimethylamides under irradiation or warming condition. By using the hemiaminal derivatives, indoles bearing a ( N ‐alkyl, N ‐methylamino)methyl group could be smoothly obtained by the reduction of the indoles bearing a ( N ‐acyl, N ‐methylamino)methyl group through the Friedel–Crafts alkylation reaction of indoles and the hemiaminal derivatives.